PENGEMBANGAN BAHAN AJAR DENGAN PENDEKATAN ETNOMATEMATIK SUKU DAYAK UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP N 1 TOBA - Dodi Dodi; Suratman Suratman; Agung Hartoyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractCulture is developing way of life, and owned by a group of people who inherit it from a previous generation. Creative entity is a form of arts created through an artefact. The combination of artefact and math/ethnomatematic provides a new innovative knowledge for students. Subjects of the research were VIII grade students of SMPN I Toba who were selected randomly. Instrument utilised in the research were module, test and interview. Module is a teaching material containing ethnomatematical exploration. The module was complied by considering the material, writing, style, number of words, formating and module appearance. The findings in general showed that stdents had an improved math external representation ability. There was an increase of number of students who do real script aspect, satitic picture, written symbols, and spoken language as well. However, students, mastery of manipulative models remained constant. Math internal representation ability did not increase either, it remained good. These were concluded from the coding stages although there was no student who  fulfilled the indicator to the saving and information recalling stages.Keywords: ethnomatematic, internal representation, external representation, pythagoras theorem.